2021
DOI: 10.3390/polym13244274
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Formulation Based on In Situ Photopolymerized Polymer for the Treatment of Spinal Cord Injury

Abstract: Spinal Cord Injury (SCI) promotes a cascade of inflammatory events that are responsible for neuronal death and glial scar formation at the site of the injury, hindering tissue neuroregeneration. Among the main approaches for the treatment of SCI, the use of biomaterials, especially gelatin methacryloyl (GelMA), has been proposed because it is biocompatible, has excellent mechanical properties, favoring cell adhesion and proliferation. In addition, it can act as a carrier of anti-inflammatory drugs, preventing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The application of GelMA as an immunotherapeutic platform for SCI is limited, with therapeutic cell delivery and tissue regeneration instead taking the focus. [67,37,43,68,70,71] However, cell graft survival and axonal regeneration cannot occur successfully in the harsh SCI immune microenvironment. [12,109,110] Therefore, immunomodulation is a critical therapeutic approach that should be incorporated into future biomaterial-based design strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of GelMA as an immunotherapeutic platform for SCI is limited, with therapeutic cell delivery and tissue regeneration instead taking the focus. [67,37,43,68,70,71] However, cell graft survival and axonal regeneration cannot occur successfully in the harsh SCI immune microenvironment. [12,109,110] Therefore, immunomodulation is a critical therapeutic approach that should be incorporated into future biomaterial-based design strategies.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Hydrogels in particular offer an injectable platform to fill irregularly shaped SCI lesions, with post-filling in situ polymerization to immobilize or enhance structural fidelity, and tuneable biodegradability for custom therapeutic release profiles. [43][44][45] When designing a therapeutic hydrogel, it is important to consider the existence of context-specific "biocompatible" properties. For example, in SCI applications, hydrogels should; have similar mechanical properties to those of spinal cord tissue with local regions as low as 70-130 Pa; [46][47][48] exhibit minimal swelling to avoid increased intraspinal pressure; [49,50] and be biodegradable with non-toxic by-products.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Novais et al (2021) further developed a GelMA-hydroalcoholic extract of red propolis (HERP) formulation (the main bioactive maker of the formulation is FMN), and verified the function of the formulation in the experimental model of rat SCI. The results showed that the formulations containing FMN had greater post-injury recovery rates compared to formulations without FMN.…”
Section: Spinal Cord Injurymentioning
confidence: 99%